Extrapolative income expectations and retirement savings - Cota, Marta (Review of Finance, 2025)
Abstract This article examines how biased income expectations affect annual contributions to retirement accounts, highlighting variations across income levels. Empirical findings show that low-income workers are generally pessimistic about future earnings, whereas high-income workers tend to be overly optimistic. I develop a lifecycle model that merges these expectation biases with US 401(k) plan features. The model reveals that biased expectations can account for observed delays in retirement contributions, which increase gradually with tenure. Contributions rise at different rates, with low-income workers starting later than high-income workers. Policy simulations indicate that automatic enrollment boosts initial contributions but results in a relative decline compared to active enrollment. Nonetheless, cumulative savings increase by 4.8 percent on average, with gains surpassing 10 percent for the lowest income quartile. These results highlight the significance of addressing income expectations in retirement policies and show that automatic enrollment can enhance welfare, particularly for lower-income individuals.